1994
DOI: 10.1126/science.8272870
|View full text |Cite
|
Sign up to set email alerts
|

Location of cAMP-Dependent Protein Kinase Type I with the TCR-CD3 Complex

Abstract: Selective activation of cyclic adenosine 3',5'-monophosphate (cAMP)-dependent protein kinase type I (cAKI), but not type II, is sufficient to mediate inhibition of T cell replication induced through the antigen-specific T cell receptor-CD3 (TCR-CD3) complex. Immunocytochemistry and immunoprecipitation studies of the molecular mechanism by which cAKI inhibits TCR-CD3-dependent T cell replication demonstrated that regulatory subunit I alpha, along with its associated kinase activity, translocated to and interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 24 publications
(5 reference statements)
4
121
0
Order By: Relevance
“…PKA type I is necessary and sufficient to confer cAMP-dependent inhibition of lymphocyte proliferation induced through the antigen receptor of T cells (26). A distinct redistribution and colocalization of PKA type I to the antigen receptors in both T cells (27) and B cells (28) is observed, supporting the notion of an isozyme-specific effect of PKA type I. Whether such direct interactions of PKA type I to receptors are limited to "mitogenic" receptors and proliferative responses or may be a general phenomenon of all antigen receptors is not known.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…PKA type I is necessary and sufficient to confer cAMP-dependent inhibition of lymphocyte proliferation induced through the antigen receptor of T cells (26). A distinct redistribution and colocalization of PKA type I to the antigen receptors in both T cells (27) and B cells (28) is observed, supporting the notion of an isozyme-specific effect of PKA type I. Whether such direct interactions of PKA type I to receptors are limited to "mitogenic" receptors and proliferative responses or may be a general phenomenon of all antigen receptors is not known.…”
mentioning
confidence: 66%
“…PKA type I-mediated inhibition of receptor-induced B and T cell proliferation is accomplished by a distinct redistribution and localization of PKA type I to the antigen receptor complexes in these cells. PKA type II, on the other hand, localizes mainly to the centrosomes in lymphocytes and is therefore more likely to serve a completely different function in these cells (27,41). Thus, PKA type I may play an important role in all lymphoid cells as a negative regulator of receptor-induced cell proliferation and function in lymphoid cells.…”
Section: Activation Of Pkc By Tpa and Ionomycin Reverses The Inhibitomentioning
confidence: 99%
“…R I ␣ is also enriched in the neuromuscular junctions (7). Type I holoenzyme is also depleted from the cytoplasm and accumulates at the ''cap'' site when lymphocytes are stimulated with anti-CD3 antibodies (8). R I was also found to associate with activated B cell receptors (9).…”
mentioning
confidence: 93%
“…This cAMP-dependent inhibition is mediated by the type I PKA [9]. Immunocytochemistry and immunoprecipitation studies on T lymphocytes have shown that cAMP induces the translocation of type I PKA and promotes its interaction with the antigen specific T cell receptor-CD3 complex [10]. It has been hypothesized that a type I PKA-mediated phosphorylation may induce uncoupling of TCR-CD3 complex from the intracellular transduction pathways [10].…”
Section: Introductionmentioning
confidence: 99%
“…Immunocytochemistry and immunoprecipitation studies on T lymphocytes have shown that cAMP induces the translocation of type I PKA and promotes its interaction with the antigen specific T cell receptor-CD3 complex [10]. It has been hypothesized that a type I PKA-mediated phosphorylation may induce uncoupling of TCR-CD3 complex from the intracellular transduction pathways [10]. Additional early steps in T lymphocyte activation, such as stimulation of phospholipase C and tyrosine phosphorylation of the ppl00 phosphoprotein, are inhibited by an increase in intracellular cAMP [11].…”
Section: Introductionmentioning
confidence: 99%